NEGATIVE HARMONY - Ponglertwut, Nanthakorn; Tanasansopin, Khaekhai; Trakulhun, Wiboon (Mahidol Music Journal, 2024)
During early 21st century, negative harmony was developed based on the basic concepts of Ernst Levy's theory of harmony which was later adapted and popularized by Jacob Collier. The basic concept of negative harmony is to create the combination of simultaneously sounded musical notes by using the opposite polarity around the axis of symmetry across tonic and dominant in each key. A group of notes of the opposite polarity are created and can be called negative triad or negative chords. Negative harmony can be used to combine with the traditional harmony in order to create more variety, novelty and interest.